COVID-19 preventive measures showing an unintended decline in infectious diseases in Taiwan - Galvin, Cooper J. (Int J Infect Dis, 2020)
Most of the communicable diseases have contact, airborne and/or droplet mode of transsmission. Following the outbreak of COVID-19, the Taiwan government implemented the use of masks and sanitizer, as well as other preventive measures like social distancing for prevention. This public response likely contributed significantly to the decline in the outbreak of other infectious diseases.